MesoDyn and Experimental Approach to the Structural Fabrication and Pore-Size Adjustment of SBA-15 Molecular Sieves - Chen Huiyong; Wu Jianghong; Luo Shaojuan; Xi Hongxia; Qian Yu (Adsorption Science & Technology)
As the main structure-directing template, P123 performs a key role during the formation of the bimodal pore system of the micro–mesoporous silica SBA-15. In this paper, the method of mesoscopic dynamics (MesoDyn) has been applied to simulate the aggregation behaviour of the triblock copolymer P123 (PEO 20 PPO 70 PEO 20 ), and to further explore the structure-formation mechanism and analyze the feasibility of accurately adjusting the pore size of SBA-15. In particular, the effect of the synthesis temperature on the P123 micelle size in the SBA-15 synthesis process has been investigated in detail due to its importance in adjusting the pore size of SBA-15. In addition, in order to validate the simulation results, a series of SBA-15 samples were synthesized at temperatures within the range 293–328 K. The simulation results show that uniform spherical micelles of P123, composed of hydrophilic PEO coronas and hydrophobic PPO cores, can be formed in aqueous solutions. This provides a perfect explanation of the experimental findings of previous work. Moreover, it has also been found that the P123 micelle gradually expands as the temperature increases, which leads directly to an increase in the mesopore diameter of SBA-15. The relevant experimental results reported in this paper demonstrate this conclusion. Overall, the mesoscopic simulation method has been shown to be a valuable tool for exploring structure fabrication and for providing an accurate guide for adjusting the pore size of SBA-15, as well as being a strong complement and extension to the experimental approach.